(untitled) (Revista de Estudos da Linguagem, 2024)
In the variety of Portuguese spoken in the Brazilian state of Rio Grande do Sul, the second person singular pronoun “tu” occurs more frequently than the innovative pronoun “você, being “tu” considered a mark of local identity. It is, however, usually followed by verbs conjugated in the third person, having been suggested that the usage of the canonical inflection is reserved to moments of a higher formality level. This study aimed to bring empirical data regarding how formal the different second person pronouns are interpreted by native speakers, as well as data confirming if they consider “tu” as part of their identity. A word selection task and a 5-point scale formality judgement task were conducted with 233 participants. The results confirm the idea that “tu” is part of the speakers’ identity and they also suggest a triadic system, composed, in order of formality by “tu”, “você”, and “o senhor”, all of them followed by a third person inflectional morphology, whereas“tu” followed by the canonical inflection competes with “você” for the intermediate position. Among the sociolinguistic factors that influence such judgments, only age was relevant, since participants who were 50 years old or older tended to consider sentences with “tu” more informal, regardless of the inflection associated to it.